Revitalisasi Pendidikan Islam Tradisional Dalam Era Transformasi Digital - Mulyadi; Inayati, Mahfida; Nor Hasan (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
This research aims to find out about the revitalization of traditional education in the era of digital transformation. This research uses qualitative research with an observation method carried out at one of the Islamic boarding schools, namely pp ummul quro plakpak pegantenan pamekasan. Thus, the results of the study can be seen that the revitalization of traditional Islamic education can be carried out in the era of digital transformation even though there are some disadvantages and advantages in its implementation. Traditional Islamic education at this Islamic boarding school began to revitalize learning media that used to use a whiteboard as a learning tool but with the existence of Digital Transformation, the media of strengthening in learning the yellow book uses a projector or LCD. So that in learning it is easy to give understanding to students. Not only that, traditional Islamic education can also be known to the public with the existence of social media that makes it easier.